Porphyromonas gingivalis Uses Specific Domain Rearrangements and Allelic Exchange to Generate Diversity in Surface Virulence Factors - Dashper, Stuart G.; Mitchell, Helen L.; Seers, Christine A.; Gladman, Simon L.; Seemann, Torsten; Bulach, Dieter M.; Chandry, P. Scott; Cross, Keith J.; Cleal, Steven M.; Reynolds, Eric C. (Frontiers in Microbiology, 2017)
Porphyromonas gingivalis is a keystone pathogen of chronic periodontitis. The virulence of P. gingivalis is reported to be strain related and there are currently a number of strain typing schemes based on variation in capsular polysaccharide, the major and minor fimbriae and adhesin domains of Lys-gingipain (Kgp), amongst other surface proteins. P. gingivalis can exchange chromosomal DNA between strains by natural competence and conjugation. The aim of this study was to determine the genetic variability of P. gingivalis strains sourced from international locations over a 25-year period and to determine if variability in surface virulence factors has a phylogenetic basis. Whole genome sequencing was performed on thirteen strains and comparison made to ten previously sequenced strains. A single nucleotide polymorphism-based phylogenetic analysis demonstrated a shallow tri-lobed phylogeny. There was a high level of reticulation in the phylogenetic network, demonstrating extensive horizontal gene transfer between the strains. Two highly conserved variants of the catalytic domain of the major virulence factor the Kgp proteinase (KgpcatI and KgpcatII) were found. There were three variants of the fourth Kgp C-terminal cleaved adhesin domain. Specific variants of the cell surface proteins FimA, FimCDE, MfaI, RagAB, Tpr and PrtT were also identified. The occurrence of all these variants in the P. gingivalis strains formed a mosaic that was not related to the SNP-based phylogeny. In conclusion P. gingivalis uses domain rearrangements and genetic exchange to generate diversity in specific surface virulence factors.